The heterogeneity of vulnerability in public health: a heat wave action plan as a case study. Issue 5 (20th October 2018) - Benmarhnia, Tarik; Alexander, Stephanie; Price, Karine; Smargiassi, Audrey; King, Nicholas; Kaufman, Jay S.
Abstract: The concept of vulnerability is frequently used in public health policies to develop tailored interventions or dedicate proportionately more resources to certain sub-populations. However, once segments of the population are identified as vulnerable, they are rarely consulted regarding whether this label is acceptable before instituting interventions. Instead, it is implicitly assumed that the targeted individuals identify themselves as vulnerable and experience an unambiguous and consistent need for public health assistance. In this paper, using public health interventions during heat waves as a case study, we question such assumptions. A qualitative study was conducted in Montreal, Canada involving two focus groups among populations specifically targeted by the heat action plan as vulnerable: one composed of individuals diagnosed with schizophrenia, and one composed of individuals who have alcohol or drug addictions. Findings revealed significant heterogeneity in the definition and experience of vulnerability as it is used in the context of a heat action plan in Montreal. We found differences between the two focus groups in several areas including sources of information they had access to within the heat action plan measures and their perspectives regarding the appropriateness of specific measures in the heat action plan. We then observed differences within each of the focus groups in several areas including their social networks relationships. The concept of vulnerability is often used in public health policies. Yet, while this concept may be convenient for shaping policies to reduce inequalities in health, the heterogeneity of populations defined as vulnerable should not be underestimated.